(untitled) (Transport systems and technologies, 2022)
Ports are the basis of the infrastructural framework of the global system of international transportation. That is why questions regarding the functioning and development of ports are always relevant. For the formation of theoretical foundations and effective mechanisms of port management, it is important not only to analyze the current state of transport networks and port systems, individual ports and their infrastructure, but also to analyze the processes of the emergence, formation, functioning and development of ports. The results of such a retrospective review from the perspective of a critical analysis of the relevant historical experience contribute to the formation of a systemic view of the prospects for the development of domestic ports. After all, prospective and retrospective analyzes are closely related. Without a retrospective analysis, it is impossible to objectively understand the prospects of the movement of this or that port on the way of its further development. The paper examines the management systems that operated during the period of Ukraine’s independence in its ports, analyzes the current status of domestic ports, and also conducts an analysis of existing approaches to the periodization of port development processes in the world. This was done in order to form the theoretical foundations of the spatial and functional evolution of ports: from the standpoint of a systemic view of the processes and possible directions of their future development; on the basis of methods of retrospective analysis of theoretical models existing in the world and systematized in the work, each of which at the empirical level can be chosen by a decision-maker as a visual "template" of the development of a specific port, taking into account the current state and existing realities.